Sintesis dan Karakterisasi Zeolit X dari Fly Ash Batu Bara Menggunakan Metode Sintesis pada Suhu Rendah: Synthesis and Characterization of Zeolite X From Fly Ash Waste Using Synthesis Method at Low Temperature - Rieswana, Yuried; Aisyah, Aurela Naura; Sani; Suprihatin (KOVALEN: Jurnal Riset Kimia, 2024)
Many industries in Indonesia have switched to using coal fuel. The use of coal at PT PLTU Paiton has reached 250 tons per hour and produces 4% of waste by-products of combustion contained from bottom ash by 25% and fly ash by 75%. Fly ash waste will harm the environment and health. Fly ash contains many components, including SiO2 52%, Al2O3 31.86%, Fe2O2 4.89%, CaO 2.68%, and MgO 4.66%. This research aims to synthesize and characterize zeolite X from PT Paiton fly ash using a low-temperature synthesis method. Zeolite X synthesis in this study has 3 steps: The pretreatment process, silica synthesis process, and zeolite synthesis process. The results of silica synthesis obtained SiO2 55.54%. The resulting zeolite product has a typical peak at 2Ï´ 28.72. Zeolite x has a wavelength of 430, 570, 695,7, and 965,7, which respectively indicates Si-O-Si and Si-O-Al bonds, double ring bonds, T-O ring symmetric strain (internal), and asymmetric (internal). The results of zeolite X crystal synthesis in this study could not be formed in the variable of adding time of 3-5 hours with a variation of moles of Al2O3 0,5-1,5 moles.